Postimplantation Syndrome after Traumatic Internal Carotid Artery Pseudoaneurysm Repair with Stent - Antonio Romanelli; Antonella Langone; Veronica Vicinanza; Renato Gammaldi (Journal of Neuroanaesthesiology and Critical Care)
Endovascular repair of traumatic internal carotid artery pseudoaneurysm (TICAP) with covered stents represents a safe treatment with few complications. However, the presence of foreign material used to treat TICAP and blood clots in the excluded pseudoaneurysms can trigger an acute systemic inflammatory response syndrome called postimplantation syndrome (PIS). To the best of our knowledge, PIS is described only after abdominal aortic endovascular aneurysm repair. Here, we report the case of PIS in a young, healthy, polytraumatized female patient with TICAP treated with endovascular covered stent.